The Relationship Between Field Clinical Practice Experience And Work Readiness Of Final Level Anesthesiology Nursing Students In Yogyakarta - Wahyuaji, Gita Latifah; Handayani, Nia; Rohmah, Astika Nur (Program Studi Sarjana Kesehatan Masyarakat Universitas Prima Indonesia, 2025)
Field Clinical Practice (PKL) is an important stage in Anesthesiology Nursing education to equip students with technical skills and work readiness. Students are required to have competence in anesthesia management. However, students' work readiness after undergoing PKL is still a question, so this research needs to be carried out. This study aims to determine the relationship between PKL experience and work readiness of Anesthesiology Nursing students in Yogyakarta. This research uses quantitative methods with a correlational design and approach cross-sectional. The research population was final year Anesthesiology Nursing students at UNISA and the Yogyakarta Ministry of Health Polytechnic. The sampling technique uses stratified random sampling, with a total of 60 respondents. Data analysis was carried out using a correlation test Spearman Rank. Based on the results of statistical analysis, the results showed that 50 students (83.3%) had PKL experience in the good category, with 52 students (86.7%) in the ready category for work readiness. Correlation test results Spearman Rank The value obtained was 0.825** and the Sig (2-tailed) value between the PKL Experience and Work Readiness variables was 0.000 (p<0,05). There is a very strong relationship between PKL experience and job readiness of final year Anesthesiology Nursing students in Yogyakarta.